A comparative study between first generation and second generation antipsychotics over the development of metabolic syndrome in persons with first episode drug naive schizophrenia - N., Pakkiyalakshmi; M., Suriyamoorthi; J., Ravishankar (International Journal of Research in Medical Sciences, 2018)
Background: Antipsychotic treatment for schizophrenia is prone for drug side effects. Both typical and atypical antipsychotics are prone for metabolic derangements. The aim of this study was to compare the emergence of metabolic syndrome with haloperidol and risperidone in drug naïve first episode schizophrenics. Methods: This was a prospective observational study conducted at the Institute of Mental health, Chennai, India from April 1, 2011 to November 15, 2011. 24 patients received haloperidol and 29 patients received risperidone and followed up for 6 months, after obtaining informed consent. PANSS score, AHA criteria for metabolic syndrome, plasma glucose, waist-hip ratio, body mass index and lipid profile were recorded at every two months interval. Results: PANSS score showed a decrease in both groups, systolic blood pressure showed an increase with Haloperidol and an initial decrease with risperidone while diastolic blood pressure increased with haloperidol. Weight gain, increase in waist circumference and hip circumference, rise in triglyceride levels and fall in HDL cholesterol were equally observed in both groups. Increase in plasma glucose was seen more with risperidone (93.1%). 18.86% (n = 10) developed metabolic syndrome at the end of 6months with no difference in emergence between both groups. Conclusions: Risperidone may be considered equivalent to haloperidol in efficacy and with minimal changes in metabolic profile. Blood pressure lowering effect of risperidone is more marked in earlier months warranting patient education. Stringent guidelines are needed during antipsychotic treatment to prevent cardiovascular and cerebrovascular morbidity and mortality.